Development of Augmented Reality-Based EduTV Interactive Visual Media on Ecosystem Materials to Improve Elementary Students' Science Literacy - Rahmahtiawati Marfiyannur Rahmandita; Wati Sukmawati (Postgraduate, University of Mataram, 2026)
This study aimed to develop Augmented Reality (AR)-based EDUTV interactive visual media on ecosystem materials and evaluate its feasibility for improving elementary students' science literacy. The study employed a Research and Development (R&D) approach adapted from the 4D model, consisting of the Define, Design, Develop, and Disseminate stages. The participants were fifth-grade elementary school students. Data were analyzed using descriptive quantitative methods based on expert validation, media feasibility assessments, and student response questionnaires. The results showed that the developed media was highly feasible for classroom use. Material expert validation yielded a feasibility score of 96%, while media expert validation obtained a score of 92%, both categorized as excellent. Student responses indicated positive perceptions toward the media presentation (88.8%), science literacy-oriented content (90.0%), and learning motivation (91.7%). These findings demonstrate that the AR-based EDUTV interactive visual media is valid, feasible, and effective for supporting Science and Social Studies learning on ecosystem topics while enhancing elementary students' science literacy. The study also contributes to achieving Sustainable Development Goal 4 (Quality Education) through innovative digital learning.